Can Partial Cultivation of Only The Sugarcane Row Reduce Carbon Dioxide Emissions in an Oxisol and Ultisol?. (1st May 2017) - Castro de Souza, Luma; Fernandes, Carolina; Santos Nogueira, Deise Cristina; Moitinho, Mara Regina; da Silva Bicalho, Elton; La Scala, Newton
Abstract : Core Ideas: The use of soil management at line (alone) reduces the CO2 emission. The higher soil aggregation favorece the higher CO2 emission. The soil management at line (alone) improve the lower soil desegregation. The objective was to determine the influence of partial cultivation of only the crop row on carbon dioxide (CO2 ) emissions in an Oxisol and Ultisol. The experimental design was a large paired‐plot design with treatments consisting of targeted chiseling to only the planting row to chiseling the whole field. Soil CO2 emissions, soil temperature, and soil moisture were measured daily for 12 d after tillage. In the Oxisol, CO2 emissions were higher on the second day after tillage and then decreased until Day 6. When analyzing the effect of tillage, chiseling in the planting row (CPR) showed, in general, lower CO2 emissions (2.54 µmol m −2 s −1 ) when compared to chiseling in total area (CTA) (3.32 µmol m −2 s −1 ), regardless of the day after tillage. However, the linear regression analysis between soil CO2 emissions and soil moisture in the Ultisol was significant for CPR ( R 2 = 0.79, p < 0.01) and CTA ( R 2 = 0.58, p < 0.01). Total soil CO2 emissions were higher in the Oxisol for both tillage systems (CPR = 1020.9 kg CO2 ha −1 and CTA = 1336.3 kg CO2 ha −1 ) than the Ultisol (CPR = 587.0 kg CO2 ha −1 and CTA = 649.3 kg CO2 ha −1 ). These results indicate that soil tillage by using CPR favors a lower soil CO2 emission to the atmosphere and contributes to a reduction in soil degradation when cultivated with sugarcane ( Saccharum officinarum L.).